(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
While ANFO is effective for rock fragmentation, its use raises concerns regarding the environmental impact of gas emissions generated during the detonation process. This study emphasizes the need for improved predictive models for assessing the amount and types of gases and dust released during open-pit mining blasts. By understanding the relationship between blasting parameters—such as charge weight, depth, and surrounding geological conditions—and the resulting emissions, we can develop strategies to minimize atmospheric contamination. The gases produced, including harmful constituents like nitrogen oxides and carbon monoxide, contribute to air pollution and have implications for public health and environmental sustainability. Thus, the research presented herein aims to provide deeper scientific insights into the dynamics of explosive gas emissions. By analyzing the factors influencing these emissions, we can enhance blasting practices to reduce their ecological footprint while maintaining mining productivity. Furthermore, recommendations will be proposed for the adoption of alternative technologies and materials to mitigate the release of harmful gases and promote environmentally responsible mining practices.